Three new Microbacterium species isolated from the Marmara Sea mucilage event: Microbacterium istanbulense sp. nov., Microbacterium bandirmense sp. nov., Microbacterium marmarense sp. nov - Saticioglu, Izzet Burcin; Ajmi, Nihed; Coskuner-Weber, Orkid; Alpsoy, Semih; Ay, Hilal; Aydin, Fuat; Abay, Secil; Karakaya, Emre; Kayman, Tuba; Dalyan, Cem; Koca, Fatih Dogan; Tasci, Gorkem; et al. (ELSEVIER GMBH, 2025)
Three bacterial strains, Mu-43T, Mu-80T, and Mu-86T, were isolated from the 2021 and 2022 mucilage event in the Marmara Sea and were taxonomically characterized. 16S rRNA gene sequence analysis confirmed that these strains belong to the genus Microbacterium. A polyphasic approach involving genomic and phenotypic analysis was employed to determine their taxonomic positions. A polyphasic approach integrating genomic and phenotypic analyses established their taxonomic positions. M. istanbulense Mu-43T showed 99.0% 16S rRNA similarity to M. bandirmense Mu-80T, with digital DNA-DNA hybridization (dDDH) and average nucleotide identity using BLAST (ANIb) values of 22.3 % and 78.3 %, respectively. M. bandirmense Mu-80T exhibited 99.2 % similarity to M. esteraromaticum DSM 8609T, with dDDH and ANIb values of 23.6 % and 80 %. M. marmarense Mu-86T showed 97.4 % similarity to M. arthrosphaerae JCM 30492T, with dDDH and ANIb values of 20.1 % and 74.2 %. Metagenomic analysis highlighted their ecological relevance, with relative abundances of 1.43 %, 1.15 %, and 0.95 %, respectively. Further genomic analysis identified biosynthetic gene clusters associated with secondary metabolite production, including non-ribosomal peptide synthetases and terpenoid biosynthesis pathways, suggesting potential antimicrobial activity. Additionally, antibiotic resistance genes, such as ABC efflux pumps and Erm23S_rRNA methyltransferase, indicate adaptation to environmental stress. These findings indicate that these species contribute to nutrient cycling and organic matter decomposition in mucilage-affected environments. Based on genomic and phenotypic data, these strains are proposed as novel species: M. istanbulense sp. nov. Mu-43T (LMG 33297T = DSM 117065T), M. bandirmense sp. nov. Mu-80T (LMG 33295T = DSM 117210T), and M. marmarense sp. nov. Mu-86T (LMG 33293T = DSM 117066T).
Keywords: Marmara Sea; Microbacterium; Mucilage; ANNOTATION; SEQUENCE; PROPOSAL; Biotechnology & Applied Microbiology; Microbiology